Glass Packaged Mineral Water Recognition System Based On Logo Using The Histogram Of Oriented Gradients Method - Lina; Fundroo Orlando; Gloria Valerie Lao; Billy Marcelino; Jerry Ruslim (Journal of Computer Networks, Architecture and High Performance Computing, 2024)
Application of Glass Packaged Mineral Water Recognition System Based on Logo Using Method Histogram of Oriented Gradients is an application program used to introduce brands or logos of glass bottled mineral water. This application was designed on the Windows operating system and uses Python and Open CV software. The methods used in this design are Histogram of Oriented Gradients as a method for feature extraction, Method Euclidean Distance as a method for measuring similarity distance, and k-Nearest Neighbor as a method of recognizing a logo or brand. The average accuracy of the test is 13.575%.